Isolation and Characterization of cDNAs Encoding Leucoanthocyanidin Reductase and Anthocyanidin Reductase from Populus trichocarpa - Wang, Lijun; Jiang, Yuanzhong; Yuan, Li; Lu, Wanxiang; Yang, Li; Karim, Abdul; Luo, Keming (PLOS ONE, 2013)
Proanthocyanidins (PAs) contribute to poplar defense mechanisms against biotic and abiotic stresses. Transcripts of PA biosynthetic genes accumulated rapidly in response to infection by the fungus Marssonina brunnea f.sp. multigermtubi, treatments of salicylic acid (SA) and wounding, resulting in PA accumulation in poplar leaves. Anthocyanidin reductase (ANR) and leucoanthocyanidin reductase (LAR) are two key enzymes of the PA biosynthesis that produce the main subunits: (+)-catechin and (−)-epicatechin required for formation of PA polymers. In Populus, ANR and LAR are encoded by at least two and three highly related genes, respectively. In this study, we isolated and functionally characterized genes PtrANR1 and PtrLAR1 from P. trichocarpa. Phylogenetic analysis shows that Populus ANR1 and LAR1 occurr in two distinct phylogenetic lineages, but both genes have little difference in their tissue distribution, preferentially expressed in roots. Overexpression of PtrANR1 in poplar resulted in a significant increase in PA levels but no impact on catechin levels. Antisense down-regulation of PtrANR1 showed reduced PA accumulation in transgenic lines, but increased levels of anthocyanin content. Ectopic expression of PtrLAR1 in poplar positively regulated the biosynthesis of PAs, whereas the accumulation of anthocyanin and flavonol was significantly reduced (P<0.05) in all transgenic plants compared to the control plants. These results suggest that both PtrANR1 and PtrLAR1 contribute to PA biosynthesis in Populus.